2015
DOI: 10.1155/2015/853105
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic and Thermodynamic Studies on the Phosphate Adsorption Removal by Dolomite Mineral

Abstract: The efficiency of dolomite to remove phosphate from aqueous solutions was investigated. The experimental results showed that the removal of phosphate by dolomite was rapid (the removal rate over 95% in 60 min) when the initial phosphate concentration is at the range of 10-50 mg/L. Several kinetic models including intraparticle diffusion model, pseudo-first-order model, Elovich model, and pseudo-second-order model were employed to evaluate the kinetics data of phosphate adsorption onto dolomite and pseudosecond… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
41
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 30 publications
3
41
1
Order By: Relevance
“…Synthetic adsorbents, such as grapheme, active carbon fiber loaded with lanthanum oxide and a novel zeolite/lanthanum hydroxide hybrid material have high phosphate removal efficiency and capacity, whereas these high‐cost synthetic materials are restricted in their widespread application because of the large quantity consumed in the actual wastewater treatment. However, some natural materials potentially offer a cost‐effective option for wastewater treatment, for example, iron oxide, clay, calcite and dolomite . Natural adsorbent materials have lower cost compared with the synthetic products, but these minerals are often limited because of their low capacity for phosphate removal in applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Synthetic adsorbents, such as grapheme, active carbon fiber loaded with lanthanum oxide and a novel zeolite/lanthanum hydroxide hybrid material have high phosphate removal efficiency and capacity, whereas these high‐cost synthetic materials are restricted in their widespread application because of the large quantity consumed in the actual wastewater treatment. However, some natural materials potentially offer a cost‐effective option for wastewater treatment, for example, iron oxide, clay, calcite and dolomite . Natural adsorbent materials have lower cost compared with the synthetic products, but these minerals are often limited because of their low capacity for phosphate removal in applications.…”
Section: Introductionmentioning
confidence: 99%
“…However, some natural materials potentially offer a cost-effective option for wastewater treatment, for example, iron oxide, 7-9 clay, 10,11 calcite 12 and dolomite. 13,14 Natural adsorbent materials have lower cost compared with the synthetic products, 3 but these minerals are often limited because of their low capacity for phosphate removal in applications. Therefore, the exploitation of less expensive and more environmentally friendly materials for removing phosphate has become increasingly important.…”
Section: Introductionmentioning
confidence: 99%
“…All the time‐dependent SAC curves are best fitted with a pseudo‐first‐order model (Supporting Information Table ), which suggests that the adsorption is diffusion controlled in our DA composite system (Simonin, ). Previous studies using dolomite as the adsorbent have shown pseudo‐second order adsorption kinetics, which suggests the binding of the molecules onto the adsorbent surface to be the rate‐limiting step, that is, the adsorption onto dolomite was reaction‐limited (Yuan et al., ).…”
Section: Resultsmentioning
confidence: 99%
“…Using adsorbents to remove and recover P from wastewater thus presents a promising alternative if an environmentally sustainable and economically viable adsorbent can be designed. To date, different types of natural minerals or synthetic adsorbents, such as iron oxide, palygorskite, magnetite, dolomite, and biochar, have been extensively tested for their P removal efficiency (Gan, Zhou, Wang, Du, & Chen, 2009;Karaca, Gürses, Ejder, & Açıkyıldız, 2006;Rashid, Price, Gracia Pinilla, & O'Shea, 2017;Shepherd, Sohi, & Heal, 2016;Suresh Kumar et al, 2017;Wan, Wang, Li, & Gao, 2017;Wang, Chen, Yu, Hu, & Feng, 2016;Yao, Gao, Chen, & Yang, 2013;Yuan et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Several methods have been introduced to the removal of phosphorus from wastewater and the commonly used techniques include precipitation (Chen and Zhuang, 2003), biological treatment (Wang et al, 2009), use of synthetic organic and inorganic chemical and adsorption (Liu and Hesterberg, 2016;Babayemi and Onukwuli, 2016). Adsorption on activated carbons has been considered, among others, to be more dependable and effective due its simplicity and cost effectiveness (Xiaoli et al, 2015;Yin and Cui, 2006 Activated carbons are mostly produced from carbonaceous materials such as palm nut (Joseph and Philomena, 2011), sawdust (Zeng et al, 2004), prawn shell (Nafaa, 2002), animal bone, palm kernel shell and other raw materials. Their distinctive adsorption properties result from their high surface areas, adequate pore size distributions, broad range of surface functional groups and comparatively high mechanical strength.…”
Section: Introductionmentioning
confidence: 99%